Branding And Re-Branding Training To Enhance The Competitive Capabilities Of Small And Medium Enterprises (SMEs) In The Digital Era: Pelatihan Branding dan Re-Branding untuk Meningkatkan Kemampuan Bersaing UMKM di Era Digital - Nabilah Ainur Rohmah; Gyska Indah Harya; Eko Nurhadi; Kenny Prizky Purba; Maysaroh Tri Khusnah; Wahyu Santoso (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Micro, small, and medium enterprises (MSMEs) are economic activities managed independently by individuals, family groups, or limited-scale business entities. Despite being the backbone of the national economy, 33.3 percent of MSMEs still rely on conventional marketing. Branding and re-branding training can be carried out to improve the competitiveness of MSMEs in the digital era. This community service program aims to overcome the digitalization challenges faced by MSMEs in Purwodadi Village, Blimbing. The activities are designed in four structured stages, namely needs analysis, program design, implementation, and evaluation. The training modules cover the basics of branding, digital content creation, WhatsApp Business optimization, and product sticker design. The results showed a 45 percent increase in the use of digital platforms, significant improvements in digital branding, and packaging professionalism. As many as 95 percent of participants successfully adopted WhatsApp Business for their marketing strategies. This initiative creates a sustainable digital learning ecosystem, driving economic, social, and technological transformation. Future plans include expanding the program to other communities and improving e-commerce capabilities.